Electrochemical Reduction of Industrial Baths Used for Electropolishing of Stainless Steel - Paweł Lochyński; S. Charazińska; E. Łyczkowska-Widłak; A. Sikora; M. Karczewski (Advances in Materials Science and Engineering)
Long-term exploitation of industrial electropolishing baths may contribute to the emergence of surface defects and may limit the range of applicable current densities. Due to this, extending the time of use of industrial baths is a major challenge. The application of electrochemical reduction in the process of reduction industrial baths enabled to reduce its contamination and, as a result, to enhance the surface quality of electropolished samples of grade 304 stainless steel. The contamination influence of the electropolishing bath on such parameters of the electropolished samples as roughness, gloss, mass reduction, and corrosion resistance was compared. The conducted tests included reduction of the contaminated industrial bath with use of cathodic reduction and monitoring of bath contamination with use of emission spectrometry ICP-OES. Potentiodynamic tests in 0.5 M chlorine environment with the aim to determine the influence of electrochemical reduction of the plating bath on surface resistance demonstrated that the pitting corrosion resistance of samples electropolished in a bath after reduction was reduced by approximately 0.1 V in comparison with samples electropolished before reduction. The calculations conducted for 24 corrosion resistance measurements demonstrated that differences between the results were significant. Bath reduction leads to improved roughness and gloss, even by approximately 500 GU (gloss units). At the same time, mass reduction decreases even by 13% in comparison with the process conducted in the bath before reduction. This may have a positive influence by slowing down the bath contamination process and, as a result, it reduces negative environmental impact. Another argument that supports the reduction of industrial baths is slowing down the process of cathode contamination during the electropolishing process. In industrial conditions, this may extend the possibility to conduct the process without the need for cathode reduction or replacement.